Uma análise lingüístico-discursiva do documento programático do P-SoL, Partido Socialismo e Liberdade - Weber, Suely (2008)
In this work we`ll present a linguistic-discourse analysis of the Programmatic Document of the Left Front P-SoL PSTU PCB, which gave support as a government program to the political campaign for the Republic Presidency of the candidate Heloisa Helena, in the 2006 elections. The reason that motivated us to make this study, was the crisis and the transformation being experienced by one of the largest and most popular political party that Brazil ever had in this national scenery, the PT, and the consequent establishment of the new party, the P-SoL, Partido Socialismo e Liberdade, among the dissidents of the PT itself. Therefore we understand that a linguistic-discourse analysis that could point out in actual texts for the movements of constitution of the new party be able to be useful for a better understanding of the current country s political party overview. This necessity has come from the core of a generalized anxiety from part of the Brazilian left parties to find or to rediscover a new route. For that we have based on theoretic point of view of the Global Semantics which dictates this Programmatic Document, in other words, the analysis of the different levels of the speech carrying the notion of manner of speech, ethos, scenography interspeech as well as the categories of analysis, among them the identification of the person`s embreantes, the types and the denial. The theory fundaments which will support this analysis will be turned for the French Discourse Analysis, with emphasis to Maingueneau studies. As an analysis procedures, we take the Programmatic Document of P-SoL, which has an introduction composed by 15 items and 4 team blocks which the distribution is the following: The macroeconomics alternative (pages 10-28); The dynamic of the new cycle (pages 29-34); The distribution of income and wealth (pages 35-41); and Population and Territory (pages 42-45). We have two objectives in this research: the first one is to analyze the interdiscourse of the Programmatic Document of the P-SoL, in order to attach into the controversial relation which is being established between the new speech and the discursive formation of the PT. The second is to analyze the P-SoL`s ethos in the document, ethos initially established to be established as a reborn identity of the Brazilian left; and by interdiscourse, the PT`s ethos, party of which P-SoL is a dissident